2018
DOI: 10.1002/jcla.22437
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between neutrophil/lymphocyte ratio and Ranson score in acute pancreatitis

Abstract: Quick diagnosis is essential in AP. Current scoring systems for AP diagnosis are complicated, whereas NLP is a simple, practical, and effective marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…A few studies have investigated the relationship between NLR and outcome in patients with AP. Abaylı et al analyzed 435 patients with AP and found that NLR was greater in the group with a Ranson score ≥3 than the group with a Ranson score <3; thus, he concluded that NLR was a simple, practical, and effective marker for diagnosis of AP severity compared with current scoring systems. O'Connell et al revealed that NLR above five increased the risk of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the relationship between NLR and outcome in patients with AP. Abaylı et al analyzed 435 patients with AP and found that NLR was greater in the group with a Ranson score ≥3 than the group with a Ranson score <3; thus, he concluded that NLR was a simple, practical, and effective marker for diagnosis of AP severity compared with current scoring systems. O'Connell et al revealed that NLR above five increased the risk of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al demonstrated that NLR is more sensitive and accurate than WBC in determining the severity of HTG-AP [18]. Abayli and Gencdal conducted a correlation study between the NLR and Ranson score on 435 AP patients and found that NLR is a simpler, more practical, and effective parameter for diagnosing the severity of AP compared with the current scoring system [22]. Li et al showed that compared with PNI, CRP, RDW, and LMR, the NLR is the most powerful indicator of overall survival and has the highest prognostic value in AP patients [9].…”
Section: Disease Markersmentioning
confidence: 99%
“…Furthermore, it is easy to obtain NLR and is less affected by physiological factors and specimen treatment [ 9 ]. Recent studies have found that NLR is closely related to the occurrence, severity, and prognoses of many acute diseases, such as acute coronary syndrome [ 10 ], acute ischemic stroke (AIS) [ 11 ], acute pancreatitis [ 12 ], acute respiratory distress syndrome [ 13 ], acute appendicitis [ 14 ], and acute type A aortic dissection [ 15 ]. During the development of systemic inflammatory response, WBCs are the effector cells of inflammatory response and the effector mediator of inflammatory conduction.…”
Section: Introductionmentioning
confidence: 99%